Municipalized education in Venezuela in sentir planetario: contribution of the local to the national land (Revista Internacional de Formação de Professores, 2023)
Municipalized Education in Venezuela is analyzed in planetary feeling as a contribution of the local to the homeland, framed in the line of research educability-municipalized university education-complex social imaginaries, from the use of the transmethod, ecosophic and diatopic comprehensive hermeneutics. The construction of a new citizenship is wanted, leaving aside that imposed by the colony, seeking the hidden, therefore, its liberation. It is a question of re-linking Municipalized Education, from the ecosophical, the ecological; it is to privilege what is ours, what is communal, what is buried and execrated in the communities.
Keywords: Education Municipalized. Transmethod. Decoloniality. Underground knowledge.